Europe unbound : enlarging and reshaping the boundaries of the European Union - Zielonka, Jan, 1955- (Routledge advances in European politics, 2003)
This book provides an analysis of the enlargement of the European Union. Drawing upon such diverse fields as history, sociology, political science and international relations.